Polymethylmethacrylate: a Review of the Implications and Complications of its Use in Orthopaedic Surgery - Anderson, G. I. (Veterinary and Comparative Orthopaedics and Traumatology, 1988)
Polymethylmethacrylate has application in the fixation of endoprostheses and void-filling in reconstructive and neurological surgery in both veterinary and human surgery. It also has extensive dental and ophthalmic applications. Literature detailing the nature of the bone/cement interface is reviewed along with the local effect of polymethylmethacrylate on bone and cartilage. The repercussions of the cellular effects of polymethylmethacrylate on the development of loosening are discussed. The immunosuppressive effects of polymethylmethacrylate to the patient are outlined. A review of the cardiovascular, pulmonary and hepatic toxicity problems of polymethylmethacrylate is included. Contact sensitisation of the user is briefly discussed in conclusion.
Keywords: Polymethylmethacrylate; Toxicity; Bone/cement interface